Risk Mapping Usahatani Melon di Brebes : Pendekatan Geo-Spasial terhadap Dampak Perubahan Iklim - Fadiyah Putri Afifah; Amirah Amirah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the forms of risk and risk management strategies in melon farming in Brebes as an impact of climate change. A descriptive qualitative approach was applied using a case study through in-depth interviews with a farmer who has more than ten years of experience, supported by secondary data from BPS, BAPPENAS, and related literature. The findings reveal four categories of major risks: market, financial, operational, and socio-environmental. High-level risks include climate variability, yield decline, and pest attacks. Medium-level risks involve production costs, water management, and price fluctuations, while low-level risks consist of limited weather information and agricultural extension services. Current strategies are still basic, including fertilization, pesticide application, and water channel arrangement. Strengthening adaptation is needed through irrigation technology, climate-resilient varieties, marketing diversification, and improved access to information and institutional support.